2021
DOI: 10.1093/pm/pnab077
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fibromyalgia Phenotype in Temporomandibular Disorders

Abstract: Background Mounting evidence suggests that central nervous system amplification, similar to that seen in fibromyalgia (FM), contributes to pain experience in a subset of patients with temporomandibular disorders (TMD). Methods In this prospective observational study, patients with TMD completed the 2011 FM survey questionnaire, a surrogate measure of “centralized” pain. The influence of centralized pain on TMD pain, dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The Fibromyalgia Survey was proposed by the American College of Rheumatology in 2010 as a way to address this issue [28]. The instrument has since been validated for evaluation of bromyalgia, temporomandibular disorders, rheumatoid arthritis, and chronic lower back pain [1,2,11]. Studies have demonstrated an association between the Fibromyalgia Survey Score, pain, and disability, even when patients have a Fibromyalgia Score below the threshold for o cial bromyalgia diagnosis [2,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fibromyalgia Survey was proposed by the American College of Rheumatology in 2010 as a way to address this issue [28]. The instrument has since been validated for evaluation of bromyalgia, temporomandibular disorders, rheumatoid arthritis, and chronic lower back pain [1,2,11]. Studies have demonstrated an association between the Fibromyalgia Survey Score, pain, and disability, even when patients have a Fibromyalgia Score below the threshold for o cial bromyalgia diagnosis [2,11].…”
Section: Discussionmentioning
confidence: 99%
“…The instrument has since been validated for evaluation of bromyalgia, temporomandibular disorders, rheumatoid arthritis, and chronic lower back pain [1,2,11]. Studies have demonstrated an association between the Fibromyalgia Survey Score, pain, and disability, even when patients have a Fibromyalgia Score below the threshold for o cial bromyalgia diagnosis [2,11]. Our study found that in patients with breast cancer, an increased Fibromyalgia Score prior to surgery is associated with ET discontinuation, with most patients discontinuing their ET due to side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in inferior frontal surface area, as well as the negative associations currently observed between ACRFS total and WPI scores and corticospinal tract volume, and between hypervigilance scores and pre- and postcentral grey matter volume, may also comport with previously published observations that orbitofrontal grey matter thickness and primary motor cortical thickness are negatively associated with pain unpleasantness and duration, respectively ( 25 , 106 ). Higher ACRFS scores were recently shown to be associated with higher levels of clinical pain, functional limitation, and disability and also with reduced responsiveness to arthroscopy of the temporomandibular joint in TMD patients ( 55 , 56 ). These central findings could help explain why the clinical pain picture is often more complex in patients with higher fibromyalgianess.…”
Section: Discussionmentioning
confidence: 99%
“…TMD is one of several chronic overlapping pain conditions believed to be driven, at least in part, by central nervous system alterations. Fibromyalgia is considered by most to be a prototypical nociplastic pain condition, and higher “fibromyalgianess” scores have been found to be associated with more complex pain mechanisms and poorer outcomes in TMD and other chronic pain conditions ( 53 56 ). Therefore, in addition to the comparisons between pain and pain-free groups, we also assessed whether TMD patients degree of likely nociplastic pain (assessed with the fibromyalgia survey criteria) is correlated with the degree of central nervous system changes.…”
Section: Introductionmentioning
confidence: 99%
“…"fibromyalgianess") in individuals who meet criteria for fibromyalgia 59 and individuals with other pain disorders who do not. 60,61 PET For all patients from both protocols, PET data were corrected for radioactive decay, deadtime, variable detector sensitivity, random coincidences, photon attenuation and scatter using software provided by the manufacturer or developed in house. Attenuation correction was performed using an MR-based approach developed in house.…”
Section: Behavioral Measuresmentioning
confidence: 99%